El discurso del Sumak Kawsay y el Gran Salto Industrial en Bolivia - Colpari, Otto (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The MAS-IPSP movement of Bolivian government of Evo Morales Ayma in the last electioneering, showed a National Government Program (2010 -2015) which outlines the key elements for future public policy in Bolivia. The goal of this study is to identify the approach of rural development of this program in a context Sumak Kawsay (“Good Life”) discursive.
Keywords: Sumak Kawsay; industry; rural development